THE EFFECT OF SEVERAL COMBINATION OF SOME TREATMENT AND METHODS OF DRYING IN QUALITATIVE CHARACTERISTICS OF DRYING APRICOTS FRUITS (Prunus armeniaca L.) - Al-Shamary, Ghalib N.; khalel , Riham I. (Diyala Agricultural Sciences Journal, 2017)
The experiment was carried out in postharvest physiology lab, at Horticulture and land scape, College of Agriculture/University of Diyala on 27/5/2014 to 2/6/2015 to study the effect of three combination of some treatment and methods of drying in two types of storage in qualitative characteristics of apricots, It was chosenas the best three combinations included: So2 with the microwave drying method (T1), NaoH with heating cabinet method (T2) and vitamin C with heating room (T3) and two types of storage (normal and radiator) and 12 month of storage. The complet randomized design C.R.D. was used in three replicated times weighted 750 – 800 g of dried fruit for each replication, the result was analyzed by using the statistical system SAS at the probability level 0.05. the fruits packaged in plastic bags were divided in two groups: the first stored in the laboratory degree heat 25ᵒ. Other, stored in chilled storage in the degree heat 1± 4. reading were taken on 8/6/2014 then after six months until the end of storage on 2/6/2015, then result showed that T2 had a significant increase in the total sugars and Tss and rate of losing weight. Whereas T3 led to decrease the percentage rate of acidity, moisture and losing weight. Chilled storage led to increase significantly the percentage of acidity, total sugars, carotene and lowest weight loss. While storage caused a decrease in the total sugars, Tss, carotene and lowest humidity loss